'Acquired' concrescence causing surgical complications – a report of two cases. (15th June 2017) - Dargue, A.
Abstract: Concrescence is a rare odontogenic anomaly. It is defined as the roots of teeth being united by cementum only. Two types of concrescence have been suggested: 'true' concrescence, which forms during tooth development, and 'acquired' concrescence, which is due to hypercementosis associated with chronic inflammation. This article presents two unsuspected cases of acquired concrescence, the first involving the roots of the upper second and third molars and the second case involving the roots of the lower second and third molars. The current literature is reviewed along with a discussion of the aetiology, typical presentation, diagnostic techniques and possible complications of this condition.